Shakespeare's domestic economies : gender and property in early modern England - Korda, Natasha (University of Pennsylvania Press, 2002)
A significant contribution to Shakespeare criticism that integrates feminism, materialist criticism, and legal history to offer an original look at how women's management of household goods became an important site of female struggle and resistance to England's patrilineal property regime. "Korda draws on the best aspects of a variety of recent critical approaches while charting new territory of her own."--Choice